Loof die Here vir sy ekosisteem: Verslag van 'n ekoteologiese Ieeservaring met Psalm 104 - G.M. Augustyn (Verbum et Ecclesia, 1997)
Praise the Lord for his ecosystem: Report on an ecotheological reading experience with Psalm 104. This article summarises the record of a conscious approach by the writer to interpret Psalm I04 with a comprehensive methodology against the available knowledge of the ecosystemic status of the world. In preparation for this reading the exegete had to reflect on his choice of exegetical method, his own being and presuppositions, knowledge on ecology itself and ecological crisis-talk, and knowledge on the place of creation theology within the Old Testament and its interpretation. A cursory representation of the outcome of the reading, regarding the structure of Psalm I04 and an example of ecotheological interpretation of the inclusio, is included.